(3TQM GdbGfhf GdeOfj (B:s (3GdYbhO GdeSeGI aj GdebGhdI,GdhcGdI,GdcaGdI (B/s - (3GdSQMGf, YOfGf GHQGgjes ((3YeGf(B: s (3ecJHI OGQ GdKbGaI ddfTQ(B, s, 2001)
(3YbO GdebGhdI(B:(3CQcGf YbO GdebGhdI, BKGQ YbO GdebGhdI, GfJgGA GdebGhdI, YbO GdhcGdI(B:(3CQcGf YbO GdhcGdI ,BKGQ GdhcGdI, GfJgGA GdhcGdI, YbO GdcaGdI(B:(3CQcGf GdcaGdI, BKGQ GdcaGdIs
(3HHdhZQGajG U(B.242s
Keywords: (3GdbGfhf GdeOfjs; (3GdcaGdIs; (3YbhO GdebGhdIs